Nickel removal from synthetic wastewater by novel zeolite-doped magnesium- iron- and zinc-oxide nanocomposites by hydrothermal-calcination technique - Rashad Al-Gaashani; Haya Alyasi; Fatima Karamshahi; Simjo Simson; Yongfeng Tongb; Viktor Kochkodan; Jenny Lawler (Scientific Reports, 2024)
Abstract This study aims to modify raw zeolite with metal oxide nanocomposites to remove nickel (Ni) ions from synthetic wastewater. Novel zeolite-doped magnesium oxide (MgO), iron oxide (Fe3O4), and zinc oxide (ZnO) nanocomposites were synthesized by hydrothermal-calcination methods. The novel zeolite-doped metal oxide nanocomposites were used as adsorbents to remove Ni (II) ions from synthetic wastewater. Several advanced techniques, including X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), and vibrating sample magnetometer (VSM) were applied to study the structural, morphological, chemical, and magnetic properties of the prepared materials. Doped zeolite with ZnO, MgO, and Fe3O4 significantly enhances the removal of Ni (II) ions from synthetic wastewater. The zeolite-doped MgO + Fe3O4 + ZnO sample achieved a Ni (II) ions removal efficiency of 99.6%, compared to 58.9% for raw zeolites. The removal efficiencies of Ni (II) ions (Ci = 30 mg/L) from highest to lowest were 99.56%, 99.53%, 91.4%, 67.8%, and 58.93% by zeolite-doped MgO + Fe3O4 + ZnO, zeolite-doped MgO, zeolite-doped ZnO, zeolite-doped Fe3O4, and raw zeolite sample, respectively. The highest adsorption capacity was 17.13 mg/g of zeolite-doped MgO + Fe3O4 + ZnO samples. The experimental adsorption data collected were fitted using five isotherm models, and four kinetic models. The Langmuir adsorption isotherm model and the pseudo-second-order kinetic model provided the best fit for the experimental adsorption data. This suggests that the adsorption process is complex, possibly involving electron interactions between the active sites of doped zeolite and Ni (II) species. The obtained data indicates that zeolite-doped with MgO, Fe3O4, and ZnO notably enhances the adsorptive properties of Ni (II) from synthetic wastewater. The obtained thermodynamic values confirmed that the adsorption process is spontaneous and endothermic, with increased randomness at the solid-solution interface during the adsorption process.